Evidence for a Two-Women Quota in University Departments across Disciplines - Lena Janys (Institute of Labor Economics (IZA), 2020)
Increasing diversity in higher tiers of occupations is a strongly debated topic and subject to legislation and reform in professional organizations in many countries. I use a novel method for detecting implicit quotas in workplaces, college admissions or birth patterns, relying exclusively on the distribution of different demographic types across different workplace locations, colleges or families. I apply this method to current employment of female professors at German universities across 50 different disciplines and show that the distribution of women, given the average number of women in the respective field, is unlikely to result from a random allocation of women across departments and more likely to stem from an implicit quota of one or two women on the department level. I also show that a large part of the variation in the share of women across STEM and non-STEM disciplines could be explained by a strict two-women quota on the department level. These findings have important implications for the potential effectiveness of policies aiming at reducing underrepresentation, as well has providing evidence how stakeholders perceive and evaluate diversity.
Keywords: J71; C15; 330; diversity; tokenism; gender; simulation methods